Pattern Of Perception And Public Participation In The Management Of Household Waste And Waste Banks In The District Of East Denpasar, Bali Province - murdiman murdiman; Made Sudiana Mahendra Sudiana Mahendra; I Made Adhika (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2017)
Efforts to reduce of waste generated by the community requires awareness, participation and cooperation among stakeholders. Denpasar Government implement strategies to manage waste handling and hygiene can be handled in each region. This step requires the integration between the systems of waste management, legal framework and clear support to be able to walk well, effectively and efficiently. On one hand, the management of solid waste management, especially those involving real role of the community, not separated from the support of government, private sector and society itself. This study was designed using descriptive analysis of qualitative and interpretative. Data was obtained through data collection techniques. Interpretative with reference to the theory and frame of mind, in order to obtain an understanding of the data in accordance with the purpose of research. Data that have been collected from questioner lets further processed and analyzed by using Likert scale and then draw conclusions, resulting descriptive data to observe the household waste management system based Waste Bank in East Denpasar District. In principle, it was observed that the principle of the 3R (reduce, reuce, and recycle) has been applied substantially in the management of household waste bins bank based in East Denpasar District involving the community. The role of the community looked to their participation in the environmental clean-up activities, including composting, bio-pore and willingness to be come a member of waste bank. The results showed that (1) the perception of the community in the management of household waste is categorized as good with an average score of 3,83 (2) community participation in the management of household waste bank-based garbage in both categories with an average score of 3,68, then used as a basis in determining strategies for the management of household waste bank based in East Denpasar District.